Trends in using Social Media as UMKM Marketing - Zakiyah, Alfina Rizkyana; Rahmanto, Andre Noevi; Sudarmo, S (Universitas Muhammadiyah Surakarta, 2023)
Purpose: This research aims to find out how the use of social media used by MSMEs for media marketing has changed from 2018-2023. Methodology: This research uses a qualitative study methodology with data analysis, namely literature study. Results: The results of this research are that many MSMEs use social media as their marketing and the one that is often used is Instagram. They also use other social media such as Facebook, WhatsApp and e-commerce. From 2018 to 2023, Instagram was ranked first, however, some MSME owners still use WhatsApp and Facebook as promotional media.